(untitled) (Fiep Bulletin - online, 2014)
The term agility we understand as complex psychomotor skills, the development of which requires a high degree of neuromuscular coordination. Agility training is one of the most effective and the most advanced forms of performance improvement in basketball. The work deals with the creation and experimental verification the program of development agility of player in basketball. On a group of 14 basketball players we verify the effectiveness of development funds agility. The results indicate the existence and character of the effect observed indicators. The results confirm the effectiveness differentiated means in both groups. The experimental group achieved better results in four tests (Illinois Agility, T - test Agility, Run after 6 - polygon P and jumping into a square) and the other two was not demonstrated significant efficacy compared with the control group. Acknowledgment: The article is part of a grant project KE GA ?. 029UKF 4/2011 “Model programs of motor activities aimed at the prevention and elimination of lifestyle diseases in adolescents’